Adolescent nutrition: what do pediatricians do? - Eell Ryoo (Korean Pediatric Society, 2011)
Multiple psychosocial problems and many chronic diseases of adulthood can be influenced by adolescent nutritional problems. In Korea, adolescent obesity and obesity related health risks have been increased and insufficient intakes of nutrients, such as calcium, iron and potassium, and distorted thinking about obesity are also common. However there are no comprehensive countermeasure because of the excessive burden of studies and the lack of community interest. And the nutrition guidelines that is suitable for Korean adolescent leaves something to be desired, and the pediatrician's concern is lacking yet. In the Korean dietary reference intakes 2010 that was revised according to the 2007 Korean National Growth Chart and 2007 Korean National Health and Nutrition Examination Survey, the range for adolescents is changed to the age 12-18 and dietary reference intakes of some nutrients mainly with vitamin D is changed. Recently several researches, about how school nutrition policies and media effect on eating habits and the weight concerns, and influences of public nutrition policies and fast food commercials have been actively studied to improve adolescent nutritive conditions. In this review, I summarize the dietary reference intakes for Korean adolescents that were revised in 2010, and current studies about the adolescent nutrition.